YOUNG UNIVERSITY STUDENTS AND ADDICTIONS, VILLA CLARA, CUBA - Zaita-Ferrer, Yanira (2021)
Confronting addictions through health promotion requires the joint action of professionals who have an impact on young people in the university community. Th e objective of this research consisted in diagnosing the way young university students act in the face of addictions in such a way that through health promotion, addictions can be prevented and thus promote a healthy culture in the Cuban university community of Villa Clara. Taking into account the methodological flexibility, inductive methods of qualitative-quantitative techniques were used from the theoretical to the empirical level. The research was developed in the Faculty of Health Technology and Nursing of the University of Medical Sciences of Villa Clara, Cuba, during the months of February 2020 to March 2021. Th e results obtained from the diagnosis corroborated the predominance of tobacco and alcohol consumption over the combination of drugs with alcoholic beverages, where the fi rst contacts with drugs occurred during the second decade of life, from 16 years of age, with a similar behavior in relation to the age of onset in both sexes. It is concluded that although drug use does not constitute an acute health problem in the university community of Villa Clara, it is necessary to increase health promotion actions to prevent these addictions and promote a healthy culture with a better quality of life.